ANALISA KONSEPTUAL MODEL SPIRITUAL WELL-BEING MENURUT ELLISON DAN FISHER - Raja Oloan Tumanggor (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2019)
Studi ini menganalisa lebih dekat dua model spiritual well-being (SWB) yang dikembangkan oleh Craig W. Ellison dan John W. Fisher. Dengan menggunakan metode kualitatif kepustakaan dilakukan perbandingan (komparasi) secara deskriptif antara pendekatan Ellison dan Fisher. Ellison memperkenalan model spritual well-being dengan dua dimensi, yakni religious well-being (RWB) dan existential well-being (EWB). Berdasarkan kedua dimensi itu Ellison kemudian mengembangkan alat ukur Spiritual Well-being Scale (SWBS). Sementara Fisher menampilkan model SWB dengan empat dimensi, yaitu personal, komunal, mondial dan transendental. Berangkat dari empat dimensi ini Fisher mengembangkan juga alat ukur Spiritual Well-being Questionaire (SWBQ). Ellison dan Fisher mendalami spiritual well-being bertolak dari pengalaman mereka mendampingi kehidupan spiritual jemaat yang mereka layani. Ellison memahami spiritual well-being sebagai kesejahteraan rohani yang merupakan perwujudan konkrit dari kesehatan rohani, sedangkan Fisher melihat spiritual well-being sebagai afirmasi hidup manusia dalam hubungannya dengan diri sendiri, sesama, lingkungan dan Tuhan. Fisher memiliki dimensi spiritual well-being lebih terperinci dari pada Ellison. Jadi perbedaan konsep dan dimensi spiritual well-being model Ellison dan Fisher berdampak kepada pembentukan alat ukur yang berbeda juga atas kedua model Ellison dan Fisher. Kendati ada perbedaan konsep dan dimensi spiritual well-being model Ellison dan Fisher, namun keduanya diperlukan untuk memperoleh pemahaman lebih mendalam atas model spiritual well-being. This study analyzes more closely the two models of spiritual well-being (SWB) developed by Craig W. Ellison and John W. Fisher. By using qualitative literature method a descriptive comparison was made between the Ellison and Fisher approaches. Ellison introduced the spiritual well-being model with two dimensions, namely religious well-being (RWB) and existential well-being (EWB). Based on these two dimensions Ellison then developed the Spiritual Well-being Scale (SWBS) measurement tool. Meanwhile, Fisher explained SWB model with four dimensions, namely personal, communal, mondial and transcendental. From these four dimensions, Fisher developed the Spiritual Well-being Questionnaire (SWBQ) measurement tool. Ellison and Fisher examined spiritual well-being based on their respective experience accompanying the spiritual lives of the congregations they served. Ellison understood spiritual well-being as a concrete manifestation of spiritual health, while Fisher sees spiritual well-being as an affirmation of human life in relation to oneself, others, the environment and God. Fisher explains spiritual dimension of well-being in more detail than Ellison. Therefore, the different concepts and spiritual well-being dimensions of Ellison and Fisher's models have an impact on the formation of different measurement tools than both Ellison and Fisher's models. Despite the differences in the concepts and dimensions of the spiritual well-being models of Ellison and Fisher, both are needed to gain a deeper understanding of the spiritual well-being model.